Pengaruh pemberdayaan karyawan, self efficacy dan pengembangan karier terhadap kepuasan kerja karyawan - Meylani Meylani; Tetra Hidayati; Dirga Lestari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This  research  aim  to  find  out  the  influence  of  employee  empowerment,  self efficacy and career development on employee job satisfaction PDAM Tirta Kencana Samarinda City. The sampling of this research are 74 employee from the amount of population number by 279 employee that drawn by purposive sampling method. This research use the multiple linier regression assisted IBM Statistical Product and Service Solution (SPSS) 23 for Windows Program. The result of this research show that partially from the hypothesis which submitted by the result of t test which X1 = 2,433; X2 = 3,752; X3 = 5,113. From the three hypothesis which submitted in this research. The first hypothesis, employee empowerment is significant influence on employee job satisfaction, the second hypothesis self efficacy is significant influence on employee job satisfaction, and the third, career development is significant influence on employee job satisfaction.